Circular Dichroism of Bipolarons in a Chiroptically Active Conjugated Polymer. Issue 5 (3rd May 2016) - Goto, Hiromasa
ABSTRACT: Bipolarons (dications), as charge carriers in chiroptically active poly(3, 4-ethylenedioxythiophene) (PEDOT*, * = chiral, atropisomer) prepared in cholesteric liquid crystals, were examined by circular dichroism (CD) spectroscopy. PEDOT* showed chiroptical activity in the near-IR (NIR) range indicating the existence of bipolarons with helical structure. The main-chain helicity and fingerprint texture derived from helical aggregation of the polymer at the macroscopic level are produced by the transcription from liquid crystals during the polymerization process. This is referred to as a matrix imprinting (MAT-I) process. The chiral-bipolaron (chiral-dications) state was confirmed through NIR-CD. The chiroptical activity of the bipolarons comes from the main-chain helical structure at the molecular level. A modulation of main-chain helicity due to generation of the polarons and bipolarons results in the electrochemically driven change in chiroptical activity (electro-chiroptical effect). We refer to chiroptically active charge carriers in the PEDOT* as chiralions.